2008
DOI: 10.1007/s10151-008-0443-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and gender on three-dimensional endoanal ultrasonography measurements: development of normal ranges

Abstract: Sphincter measurements, enabled by 3-D reconstruction, vary with age and sex. A normal range incorporating these variations has been produced for future data comparison in disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…In this modality, images are captured along the proximal-distal axis of the anal canal by moving two crystals on the extremity of a stationary transducer. All measurements were obtained accurately, without any interference from probe movement, and our results demonstrated very good interobserver variability due to the simplicity of length measurements, as previously described in the literature (9,13,14) . Volumetric measurements were not obtained, since they are limited by methodology, which consists of measuring the area of the anal sphincter in successive images, hindering determination of the exact lateral, proximal and distal limits of the muscles (17) .…”
Section: Eas Defect Plus Eas + Ias Defect (N = 33) Anterior Ias (Cm) Vssupporting
confidence: 79%
“…In this modality, images are captured along the proximal-distal axis of the anal canal by moving two crystals on the extremity of a stationary transducer. All measurements were obtained accurately, without any interference from probe movement, and our results demonstrated very good interobserver variability due to the simplicity of length measurements, as previously described in the literature (9,13,14) . Volumetric measurements were not obtained, since they are limited by methodology, which consists of measuring the area of the anal sphincter in successive images, hindering determination of the exact lateral, proximal and distal limits of the muscles (17) .…”
Section: Eas Defect Plus Eas + Ias Defect (N = 33) Anterior Ias (Cm) Vssupporting
confidence: 79%
“…Men have a greater striated muscle mass compared to women due to the well-known effect of testosterone on muscle growth [21]. For the external sphincter muscle, a shorter external sphincter muscle was seen anteriorly in females by MRI and 3D-EUS [22,23], while no difference in muscle thickness was measured by conventional EUS [23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…although differences in ultrasound equipment, anatomic landmarks, and/or measuring technique may have led to slight discrepancies, our length parameters were similar to those used by other investigators. 27 Previous studies used 2-dimensional ultrasound equipment, which resulted in limited length measurements. 10,11,20,28 Garcia-Aguilar et al 10 evaluated patients undergoing lis and found that the ias defect was wider in patients with incontinence than in those who were continent, but the difference was not significant.…”
Section: Discussionmentioning
confidence: 99%